Characteristics of Gas-Phase Partial Oxidation of Nascent Tar from the Rapid Pyrolysis of Cedar Sawdust at 700−800°C - Hosokai, S.; Kishimoto, K.; Norinaga, K.; Li, Chun-Zhu; Hayashi, J. (American Chemical Society, 2010)
Volatiles from the rapid pyrolysis of cedar sawdust were subjected in situ to gas-phase thermal cracking in the presence and absence of O2. It was found that O2 influenced the resulting product distribution in completely different manners at 700 and 800 °C. O2 was consumed at 700 °C mainly by the oxidation of tar and light oxygenates, forming CO, CO2, and H2O, unless the ratio of O2/carbon involved in the nascent volatiles (O/C) exceeded 0.7 mol of O/mol of C. On the other hand, the oxidation at 800 °C consumed H2 and lower hydrocarbons selectively, leaving the residual tar yield nearly unchanged. Such different behaviors of O2 were mainly due to the difference in characteristics of thermal cracking of the tar and light oxygenates between 700 and 800 °C. The thermal cracking at 700 °C left the tar with a molecular mass (MM) range up to >1000, which was decomposed in the presence of O2 but incompletely.At 800 °C, the tar was decomposed quickly even in the presence of O2, forming refractory aromatics with a MM range up to 400 together with soot, while light gases were oxidized. A portion of the tar from the cracking at 700 °C was deposited inside a ceramic-fiber filter downstream of the reactor, the temperature of which was 350−500 °C, and the deposit could not be removed mechanically. The entire part of the tar from the cracking at 800 °C was allowed to pass through the filter regardless of O/C. It was thus found that the gas-phase temperature of 700−800 °C was critical to the tar property relevant to dust removal at 350−500 °C.